Analisis Faktor Yang Mempengaruhi Anak Bekerja Di Gampong Tengah Kecamatan Kuala Batee Kabupaten Aceh Barat Daya - Yuliana (JAROW: Journal of Ar-Raniry on Social Work, 2025)
Parents are the primary and first educators for their children, because it is from them that children first receive education. Many parents use their children as a source of fulfillment for both the children themselves and their families. Some children from the middle village are still in school and some are no longer in school. They work after school hours, and some children work during school hours. This study aims to determine the factors that influence children to work in Gampong Tengah, Kuala Batee District, Southwest Aceh Regency, and to find out what causes parents to allow their children to work in Gampong Tengah, Kuala Batee District, Southwest Aceh Regency. This research method uses a qualitative approach with a descriptive research type. Data collection techniques are carried out by interviews, observations and documentation. The results of the study showed that children from the middle village who work are generally known by their parents and children who work have a family background with a fairly low economy. This is indicated by the low education of their parents, most of whom are elementary school graduates and some have not attended school at all. And the work of the parents is mostly only as farm laborers. with income that is barely enough for daily needs. The relatively low economic conditions of the family also cause parents to allow their children to work while going to school. It is undeniable that there are reasons for children to work solely because they want to help the family economy, to meet their own needs because the children of their parents do not get their rights in meeting their daily needs due to the work and income of their parents which are barely enough, another reason children work is because they want to pay for school needs